2017
DOI: 10.1088/1361-6404/aa68fd
|View full text |Cite
|
Sign up to set email alerts
|

Comment on ‘The paradoxical zero reflection at zero energy’

Abstract: We point out that the anomalous threshold effect in one dimension occurs when the reflection probability at zero energy R(0) has some other value than unity, rather than or as implied by Ahmed et al in their paper entitled ‘The paradoxical zero reflection at zero energy’ (2017 Eur. J. Phys. 38 025401).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…In this section, we use the factorisation method usually applied in supersymmetric quantum mechanics [20] to design a family of HBS supporting dielectric profiles, which do not reflect TE waves at grazing incidence. We note that our approach connects with recent work in quantum mechanics by Ahmed et al where zero energy reflectionless potentials have been investigated in several cases [34][35][36], and where HBS supporting potentials have been subject to supersymmetric transformations to generate e.g. potentials supporting no bound states at all [37].…”
Section: Factorisation Methodssupporting
confidence: 56%
“…In this section, we use the factorisation method usually applied in supersymmetric quantum mechanics [20] to design a family of HBS supporting dielectric profiles, which do not reflect TE waves at grazing incidence. We note that our approach connects with recent work in quantum mechanics by Ahmed et al where zero energy reflectionless potentials have been investigated in several cases [34][35][36], and where HBS supporting potentials have been subject to supersymmetric transformations to generate e.g. potentials supporting no bound states at all [37].…”
Section: Factorisation Methodssupporting
confidence: 56%
“…This critical well has an n-node (n 1) half-bound state at E = 0. In an interesting comment to [1], van Dijk and Nogami [2] have suggested that the exactly solvable well-barrier system of double Dirac delta potential (DDDP) can be made to have much less (non-zero) reflection at zero or low energies: R(0)…”
mentioning
confidence: 99%